JAK1/2 Inhibitors AZD1480 and CYT387 Inhibit Canine B-Cell Lymphoma Growth by Increasing Apoptosis and Disrupting Cell Proliferation - Lu, Z.; Hong, C. C.; Jark, P. C. [UNESP]; Assumpcao, A. L. F. V.; Bollig, N.; Kong, G.; Pan, X. (Wiley-Blackwell, 2017)
Background: Canine diffuse large B-cell lymphoma (DLBCL) is a common and aggressive hematologic malignancy. The lack of conventional therapies with sustainable efficacy warrants further investigation of novel therapeutics. The Janus kinase (JAK) and signal transducer and activator of transcription (STAT) pathways play important roles in the pathogenesis of hematologic malignancies in humans including DLBCLs. AZD1480 and CYT387 are novel JAK1/2 inhibitors that have been used in clinical trials for treating various hematologic cancers in humans. No studies have characterized the antitumor effects of JAK inhibitors on DLBCL in dogs. Hypothesis/Objectives: We hypothesize that JAK1/2 inhibitors AZD1480 and CYT387 can effectively inhibit growth of canine DLBCL in vitro. We aim to assess the antitumor activity of AZD1480 and CYT387 in canine DLBCL and to determine the underlying mechanisms of action. Methods: In vitro study of canine lymphoma cell growth, proliferation, and apoptosis by viability, proliferation and apoptosis assays. Results: A significant decrease in viable canine lymphoma cells was observed after AZD1480 and CYT387 treatments. In addition, AZD1480 and CYT387 treatment resulted in decreased lymphoma cell proliferation and increased early apoptosis. Conclusion and Clinical Importance: AZD1480 and CYT387 inhibit canine lymphoma cell growth in a dose-dependent manner. Our findings justify further phase I/II clinical investigations of the safety and efficacy of JAK1/2 inhibitors in canine DLBCL and suggest new opportunities for novel anticancer therapies.
Keywords: Apoptosis; Canine DLBCLs; Cell cycle; JAK inhibitors